Refractory bronchovascular pleuropulmonary mucormycosis: Case report and difficulties in management - Manjunath, M (Lung India, 2018)
Pulmonary mucormycosis is a life-threatening opportunistic fungal infection. It is considered as a disease of immunocompromised state and is rarely seen in immunocompetent patients. We here report a case of refractory bronchovascular pleuropulmonary mucormycosis, who despite early detection, optimal management with liposomal amphotericin B, and posaconazole therapy followed by surgery, progressed further and led to a fatal outcome. Dual antifungal therapy combined with surgery is the only definitive treatment option available in the literature. Many new therapeutic options for mucormycosis treatment have become available but none have shown promising results, and larger studies are required to assess their efficacy.